Experimental study of light-transmitting concrete. Issue 3 (1st October 2016) - Altlomate, Abdelmajeed; Alatshan, Faesal; Mashiri, Fidelis; Jadan, Mohamed
Abstract: This paper aims to investigate the performance of concrete which incorporates plastic optical fibre (POF). In this study, the performance of light-transmitting concrete (LTC) specimens made by using different dosages and spacings of POF is investigated. The properties of POF are investigated and discussed. The experimental results show that LTC can provide a high light-transmitting ratio. This paper contributes to the determination of new alternatives for sustainable construction around the world. LTC can help to reduce power consumption in buildings by allowing natural light to shine into the building interior through external walls. This paper adds distinctive knowledge to the area of sustainable construction by studying the effect of POF on the properties and performance of concrete. In addition, the use of POF in concrete can lead to an increase in compressive strength.